2018
DOI: 10.1186/s12882-018-0962-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum free light chain levels and renal function at diagnosis in patients with multiple myeloma

Abstract: BackgroundRenal impairment (RI) is common in multiple myeloma (MM) and is associated with poor survival. This study reports the associations between renal function and disease characteristics including serum free light chain (FLC) level at diagnosis in patients with MM.MethodsUsing data from the Medical Research Council Myeloma IX trial, a multicentre, randomized, open-label, phase III and factorial-design trial, we assessed the relationships between renal function, demographic, and disease characteristics, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…The IMWG in their recent revised diagnostic criteria for MM included RI caused by MCN as a myeloma defining event, where MCN was characterised by the presence of typical histological features or an involved Table 2 Landmark analysis of associations between haemodialysis independence and overall survival in patients with MCN (n = 69). 15 . Importantly this study showed that patients could have a very high FLC level and no RI at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IMWG in their recent revised diagnostic criteria for MM included RI caused by MCN as a myeloma defining event, where MCN was characterised by the presence of typical histological features or an involved Table 2 Landmark analysis of associations between haemodialysis independence and overall survival in patients with MCN (n = 69). 15 . Importantly this study showed that patients could have a very high FLC level and no RI at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The IMWG associated RI as a consequence of MCN to a serum FLC level above 1500 mg/ L 13 , whereas the International Kidney and Monoclonal Gammopathy (IKMG) Research Group proposed a serum FLC level above 500 mg/L 14 . We recently analysed the Myeloma IX study and found that an FLC level above 800 mg/L had the highest sensitivity and specificity for severe RI defined by an estimated glomerular filtration rate (eGFR) <30 ml/min/1.73 m 2 at diagnosis 15 . However that study did not include patients who required dialysis and information on renal histology was not available.…”
Section: Introductionmentioning
confidence: 99%
“…47 Factors that promote the formation of intratubular casts include volume depletion, metabolic acidosis, loop diuretics through the increase in tubular sodium concentration, increased urinary calcium and hypercalcemia, and radiocontrast media. 48 Sensitive assays for plasma FLCs as well as serum and urine protein electrophoresis and immunofixation facilitate the diagnosis of myeloma-related AKI. The normal plasma-free κ-to-λ ratio is 0.26 to 1.65 in patients without kidney impairment and 0.37 to 3.1 in patients with severe kidney impairment.…”
Section: Light-chain Cast Nephropathymentioning
confidence: 99%
“…The normal plasma-free κ-to-λ ratio is 0.26 to 1.65 in patients without kidney impairment and 0.37 to 3.1 in patients with severe kidney impairment. 48 Elevated FLCs in association with an abnormal κ-to-λ ratio typically indicate a monoclonal plasma cell proliferative process. The plasma FLC assay is more sensitive than urine protein electrophoresis for detecting FLCs.…”
Section: Light-chain Cast Nephropathymentioning
confidence: 99%
“…Physicochemical properties of the secreted paraprotein may determine pathological features, for which a variety of Ig-dependent and independent mechanisms have been described (see Figure 1 ) [ 8 , 14 ]. However, it has to be emphasized that FLC levels >800 mg/L are good predictors of severe RI, regardless of the paraprotein type [ 16 ]. Tools to recognize the degree of nephrotoxicity for particular monoclonal paraproteins are still lacking; therefore, very early identification of renal insult is crucial.…”
Section: Multiple Myeloma and Renal Impairment—an Overviewmentioning
confidence: 99%